A bibliometric analysis on green human capital and work engagement with emphasis on psychological ownership. - Kumari, Rashmi; Dash, Sujata Priyambada; Chatterjee, Rajeshwari (Work, 2026)
Background: Employee engagement is a crucial factor for organizational success. One effective way employers can enhance engagement is by fostering a stronger psychological sense of influence among employees. Supporting green activities or values that resonate with the workforce is a key strategy. However, the relationship between psychological ownership, work engagement, and green human capital has not been thoroughly evaluated in existing literature. Objective: The purpose of this study is to provide a comprehensive review of the literature on the relationship between psychological ownership, work engagement, and green human capital. This review aims to evaluate prior studies and identify key trends and gaps in the field. Methods: A total of 50 studies meeting the inclusion criteria were analyzed. The dataset, spanning from 2017 to 2023, was examined using bibliometric analysis. Notably, publications from publishers such as Elsevier, Emerald, MDPI, Sage, and others were excluded. The research employed VOS viewer software to conduct co-authorship, co-occurrence, and citation analyses. Results: The analysis revealed the top countries, authors, journals, and academic works in the field. It also highlighted key trends in the literature and provided insights into ongoing and future research directions. Conclusions: Psychological ownership has the potential to reduce behavioral issues and enhance employee engagement. However, the effectiveness of this outcome is contingent upon leadership styles and the support mechanisms provided by the organization.